STRATEGY FOR IMPROVING PERFORMANCE OF INFORMAL SECTORS BASED ON ECOWISATA IN WHITE SAND BEACH TOURISM IN SITUBONDO DISTRICT - Isti Fadah, Handriyono, Diana S Tobing & Istatuk BY (International Journal of Research Science and Management, 2019)
This research is more focused on an in-depth study of the fundamental problems faced by the Informal Sector in the White Sand Beach Area and the preparation of effective strategies for increasing income based on Ecotourism. This research uses a qualitative method approach. The qualitative approach is more focused on studying in depth the problems faced by the informal sector and alternative strategic models to improve performance through increased Ecotourism activities in the White Sand Beach. The results of the study indicate that the promotion of the existence of the White Sand Beach Tourist Attractions is not optimal done. Artistic attractions based on local culture and local wisdom and annual events that are able to attract tourists are not optimal in this place. The merchandise and services offered on the White Sand Beach of that type are just that, there are no significant additional innovations yet. Guidance and ongoing socialization about conservation of the White Sand Beach tourism is important to be done so that the beauty of the White Sand Beach can be enjoyed up to children and grandchildren and more interesting to visit while at the same time the income of the informal sector can be increased in line with the increase in visitors. Synergistic efforts are needed to design an integrated promotion to offer a combination of tour packages from several beach tours in Situbondo